Martin’s phosphino-triol revisited: unexpected P-C bond cleavage reactions and their suppression via complexation of Al3+ and Sc3+ - Mörsdorf, Jean-Marc; Bruckhoff, Tim; Matveeva, Regina; Rudin, Benjamin; Wadepohl, Hubert; Ballmann, Joachim (Inorganic chemistry, 2021)
A revised synthesis of Martin’s phosphino-triols (two derivatives) is reported. Once isolated, these thermally sensitive triols were shown to disassemble selectively via an unexpected P-C bond cleavage reaction. This degradation pathway was effectively suppressed via complexation of Al3+ and Sc3+. In the resulting half-cage complexes, the ligand scaffold is bound to each metal (Al3+ and Sc3+, respectively) via all four donor atoms. So far, this κ4-P,O,O′,O″-coordination mode has not been observed for any other phosphino-triol.